2005
DOI: 10.1017/s1047951105000831
|View full text |Cite
|
Sign up to set email alerts
|

Levels of brain natriuretic peptide in children with right ventricular overload due to congenital cardiac disease

Abstract: There is a significant correlation between right ventricular haemodynamic parameters and concentrations of brain natriuretic peptide in the plasma of children with right ventricular overload due to different types of congenital cardiac disease. The monitoring of brain natriuretic peptide may provide a non-invasive and safe quantitative follow up of the right ventricular pressure and volume overload in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…This has been shown in the blood of patients with congenital heart disease [13, 27, 28], but also directly in animal experiments by quantification of myocardial mRNA [29]. Some authors also found increased brain natriuretic peptides in patients with chronic right ventricular pressure load [12, 30]. However, others did not [13].…”
Section: Discussionmentioning
confidence: 86%
“…This has been shown in the blood of patients with congenital heart disease [13, 27, 28], but also directly in animal experiments by quantification of myocardial mRNA [29]. Some authors also found increased brain natriuretic peptides in patients with chronic right ventricular pressure load [12, 30]. However, others did not [13].…”
Section: Discussionmentioning
confidence: 86%
“…This view of BNP as a mirror of ventricular decompensation by volume load instead of a marker for volume load itself can also explain other contradictory reports. Some authors found increased brain natriuretic peptides in patients with chronic right ventricular pressure load [13,14], but others did not [15,19]. Isolated pressure load of the right ventricle due to pulmonary banding, pulmonary valve stenosis or uncorrected tetralogy of Fallot did not cause an increase of BNP [7,27], but right ventricular pressure load together with increased pulmonary artery pressure and resistance was associated with increased BNP [7,30].…”
Section: Discussionmentioning
confidence: 96%
“…Plasma BNP was significantly higher in females than males (median 37 [IQR 21-57] vs. 16 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] pg/ml, p = 0.001) (Fig. 1).…”
Section: Bnp and Baseline Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to be useful in the diagnosis, prognostication and refinement of management in adults with heart failure [16][17][18]20]. While previous studies have demonstrated elevated BNP level in ventricular dysfunction complicating different types of congenital heart disease [21][22][23][24][25][26], the role of plasma BNP in the assessment of systemic RV function after atrial switch operation has not been examined. The present study aimed to test the hypothesis that plasma BNP is a biomarker of systemic RV function in patients with complete TGA after atrial switch operation.…”
Section: Introductionmentioning
confidence: 99%